STUDI INTEGRASI ISLAM, SAINS DAN BUDAYA NUSANTARA DI MADRASAH IBTIDAIYAH - Putri Nazma Maharani (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2018)
Integration or Islamization of knowledge are now beginning to develop among Muslim intellectuals. They also hold religious awareness, and that science is in harmony with God's revelation. Science needs to be transformed to believe in the grace that He has given. In an effort as a science development, it is necessary to improve the activities of the teaching and learning process so that the Madrasah Ibtidaiyah arises. Islamic elementary schools have an important role to balance between science and general science. Madrasas as educational institutions that grow and develop from the tradition of religious education in society. In the past the first Islamic Education Institution was established in Indonesia in the form of pesantren. Pesantren has become a tradition or culture that is attached to society as the foundations for laying out Islamic education. Starting and developing from pesantren education, Madrasah Ibtidiyah is the initial foundation for putting knowledge on children. Islamic elementary schools also play a role in developing a process of learning activities that integrate Islamic education, national science and culture Key word:.Integration of Islamization, Science, and Culture